PERSPECTIVES OF HEALTH ASSISTANTS AND NURSING TECHNICIANS ON SAFE AND HIGH QUALITY PATIENT CARE IN SAUDI ARABIA: A MIXED METHODS STUDY - Radhi Alawi Saoaib Aldhafeeri, Naif Salman Khabour Aldhafeeri, Fahad Eid Nughaymish Aldhafeeri, Tahani Munawir Moklef Aldhafeeri, Abdaaziz Dugaim Salim Aldhafeeri, Fadhela Faraj Fares Aldhafeeri, (Chelonian Research Foundation, 2022)
Health assistants and nursing technicians fulfill indispensable roles in healthcare delivery, yet their perspectives are rarely elicited in Saudi Arabia. This convergent parallel mixed methods study aimed to examine the views of these frontline providers on elements enabling safe, high quality patient care in their settings. Surveys and semi-structured interviews were conducted with 75 health assistants and nursing technicians at 3 hospitals. Quantitative results indicated that strong teamwork and communication were rated as having the most substantial impact on safe, quality care delivery. Qualitative themes that emerged emphasized needs for sufficient staffing, manageable workloads, continuing education on evidence-based practices, supportive leadership, and engagement of assistants and technicians in quality improvement initiatives in order to optimally provide care. Integrated findings highlight key strategies to strengthen the capacities of health assistants and nursing technicians through robust training programs, fostering collaborative team practice, implementing workflow improvements, and promoting greater involvement of these allied health professionals in care enhancement efforts.